SPORT DOPING : KNOWLEDGE OF ATHLETES FROM SPORT SCIENCE FACULTY UNESA - indra himawan susanto (Universitas Negeri Yogyakarta, 2025)
This study aims to determine the doping knowledge of athletes from the Faculty of Sports Science, State University of Surabaya. This research is quantitative and descriptive. The method used in this research is a survey with a closed questionnaire collection technique. The data obtained with this closed questionnaire was processed by quantitative descriptive statistical analysis and categorization using a frequency distribution table. The results showed that the level of knowledge of FIO Unesa student-athletes in the good category was 18 athletes (37.51%), in the sufficient category as many as 26 athletes (54.16%), and in the less category as many as 4 athletes (8.33%). The conclusion that can be drawn in this study is that the athlete's knowledge of Anti-Doping is very important for athletes in understanding knowledge about Anti-Doping so that athletes do not use doping in increasing or achieving an achievement because doping does not guarantee a maximum achievement.